TINDAKAN KEPOLISIAN DALAM PENANGGULANGAN TINDAK PIDANA PERJUDIAN DI WILAYAH HUKUM KEPOLISIAN DAERAH SUMATERA UTARA - Nopitasari Wulandari; Mangasa Manurung; Bachtiar Simatupang (JURNAL PROINTEGRITA, 2019)
The purpose of this study was to find out and understand the factors that led to gambling crime in the Regional Police of North Sumatra, the efforts of the North Sumatra Regional Police in overcoming gambling in the North Sumatra Regional Police, the obstacles experienced by the North Sumatra Regional Police overcoming gambling crime in the Regional Police of North Sumatra.The results of the research show that the factors of the occurrence of criminal gambling are factors in the individual (internal) which include the level of education, religious factors, psychology. Factors originating from outside the individual (external) Economic factors, social factors, family environment. The efforts of the police in overcoming the crime of gambling in the Regional Police of North Sumatra include: Preventive prevention efforts, Rehabilitation efforts, Refresive mitigation efforts.